Imaging biomarkers in optic neuritis: current tools and future directions - Meng, Ziwei; He, Yuhong; Guo, Kai; Li, Lin (Frontiers in Neurology, 2025)
Optic neuritis (ON), a central manifestation of multiple inflammatory central nervous system (CNS) disorders, has seen remarkable advances in diagnostic and therapeutic strategies due to rapid progress in imaging technologies. This review systematically summarizes recent high-quality literature focusing on the latest progress of optical coherence tomography (OCT), optical coherence tomography angiography (OCTA), magnetic resonance imaging (MRI), and diffusion tensor imaging (DTI) in ON. It further explores the integrative application and clinical value of multimodal imaging combined with immune biomarkers. Additionally, the application of artificial intelligence (AI) and deep learning (DL) in image analysis is discussed. This review highlights current innovations and proposes future directions for establishing multicenter standardized protocols, facilitating precision diagnostics, and promoting personalized management, thereby accelerating clinical translation and advancing neuroimmunological ophthalmology.